2022
DOI: 10.3390/en15093070
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Life Assessment of the Low-Voltage Circuit Breaker (LVCB) Considering Arc Voltage

Abstract: The low-voltage circuit breaker (LVCB) is commonly utilized in the distribution network. An accurate evaluation of its electrical life is related to the safety and reliability of electric energy output. The traditional arc erosion model only considers the effect of current on contact wear while ignoring the impact of operation conditions (supply voltage and power factor) on electrical life. As a result of the arc voltage, the original circuit topology changes, resulting in an early current zero. At 220–660 V A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…To simplify the calculation, the external circuit is equated to an RL series circuit. According to Kirchhoff's first law, the circuit equation can be obtained as shown in Equation (1).…”
Section: Control Equations and External Circuit Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…To simplify the calculation, the external circuit is equated to an RL series circuit. According to Kirchhoff's first law, the circuit equation can be obtained as shown in Equation (1).…”
Section: Control Equations and External Circuit Modelmentioning
confidence: 99%
“…From the distribution of the temperature of the arc at different moments of the ignition phase, it can be concluded that the evolution of the arc can be divided into the following stages. (1) The initial arc between the contacts in the air field and magnetic field under the action of continuous expansion, and an arc column with moving contact movement, expansion, and elongation. (2) The arc moves in the direction of the splitter, during which the arc is constantly bent and elongated, the arc voltage rises, and when it reaches the vicinity of the splitter, the arc column is squeezed by the splitter.…”
Section: Simulation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Cui et al proposed a new method of rolling bearing fault feature extraction based on improved switching Kalman filtering. After a comparison with the traditional Kalman filtering algorithm, each iteration of the method requires only the current monitoring data measurements and the optimal estimation of the previous moment, which is computationally efficient and has strong real-time performance [5].…”
Section: Introductionmentioning
confidence: 99%
“…F. Xing et al improved the prediction model by considering the influence of arc duration on contact erosion, resulting in increased accuracy [ 5 ]. Liu Z et al studied the impact of arc voltage on the electrical lifespan of circuit breakers, using Monte Carlo methods to simulate the distribution of electrical lifespan under different operations [ 6 ]. K. Huang et al proposed a fuzzy reliability-based lifespan assessment model and an improved gray prediction method based on stepwise data sequences to predict the remaining lifespan of circuit breakers [ 7 ].…”
Section: Introductionmentioning
confidence: 99%